Strong association of interleukin-6 −174G/C promoter single nucleotide polymorphism with a decreased risk of colorectal cancer in ethnic Kashmiri population: A case control study - Mujeeb Zafar Banday; Henah Mehraj Balkhi; Aga Syed Sameer; Nissar A Chowdri; Ehtishamul Haq (Tumor Biology, 2017)
Chronic inflammation increases the risk of development of various cancers, including colorectal cancer. Interleukin-6 has been described as a key regulator of colorectal cancer development and is important in the process of colorectal tumorigenesis largely through the regulation of tumor-promoting inflammation. Several studies have reported the association of various polymorphisms in human interleukin-6 gene including IL-6 −174G/C single nucleotide polymorphism with various cancers, including colorectal cancer, but the results are mixed and inconclusive. The aim of this study was to analyze the association of IL-6 −174G/C promoter single nucleotide polymorphism with colorectal cancer risk and also to evaluate the modifying effects of possible IL-6 −174G/C single nucleotide polymorphism genotypes on different risk factors of colorectal cancer or the reciprocal effect in ethnic Kashmiri population through a case control setup. The genotype frequencies of IL-6 −174G/C promoter single nucleotide polymorphism were compared between 142 colorectal cancer patients and 184 individually matched healthy controls by using polymerase chain reaction–restriction fragment length polymorphism method. The association between the IL-6 −174G/C single nucleotide polymorphism and colorectal cancer risk was examined through conditional logistic regression models adjusted for multiple possible confounding (third) variables. The possible effect measure modification of the association between the relevant single nucleotide polymorphism genotypes and colorectal cancer risk by various colorectal cancer risk factors including age, gender, and smoking status was also evaluated. Furthermore, the associations between these single nucleotide polymorphisms and various clinicopathological parameters, demographic variables, and environmental factors within the case group subjects with regard to colorectal cancer risk were also analyzed. The overall association between the IL-6 −174G/C single nucleotide polymorphism and the modulation of colorectal cancer risk was found to be highly significant (p = 0.001). The variant genotype (CC) was significantly associated with a decreased risk of colorectal cancer (odds ratio, 0.15 (95% confidence interval, 0.04–0.54); p = 0.004). Furthermore, the less common IL-6-174C allele was associated with a decreased risk of colorectal cancer (odds ratio, 0.49 (95% confidence interval, 0.33–0.73); p = 0.0006). The combined variant genotype (GC + CC) was also significantly associated with a decreased risk of colorectal cancer (odds ratio, 0.54 (95% confidence interval, 0.33–0.89); p = 0.015). This study demonstrates that there is a strong and highly significant association between the IL-6 −174G/C promoter single nucleotide polymorphism and a decreased risk of colorectal cancer in ethnic Kashmiri population. However, in order to substantiate our findings, this study needs to be replicated with larger sample size and with other ethnically defined populations with comparable colorectal cancer incidence.